Genetic resistance to fusariosis and base rot in interspecific F1 progenies of passion fruit (Passiflora spp.) (Research, Society and Development, 2020)
Fusariosis and base rot, caused by the fungi Fusarium oxysporum f. sp. passiflorae and F. solani, respectively, seriously damage the cultivation of sour passion fruit in Brazil. This work aims to obtain and evaluate F1 hybrids of Passiflora spp. wild plants resistant to fusariosis and base rot using genotypes of P. edulis (commercial species) and certify interspecific hybridizations using microsatellite markers. Hybridizations were performed using a P. edulis female parent and P. nitida and P. mucronata male parents for crosses aiming fusariosis resistance, and P. nitida, P. cincinnata and P. quadrangularis for hybridizations aiming tolerance to base rot. 35 microsatellite markers were used to confirm hybridization. The washed roots method was used for fusarium resistance tests and inoculation procedure with a mycelium disk fixed on a small wound on the plant stem for base rot. The interspecific hybridizations provided 49 potentially hybrid genotypes. Confirmation of hybridization by microsatellite marker was verified for 57% of the analyzed genotypes. The hybrids 115-1, 115-3, 115-4, 115-5, 115-6, 115-7, 115-9 and 128 are indicated as promising genotypes for a new stage of the breeding program. In the resistance evaluation of 13 F1 hybrids to F. oxysporum f. sp. passiflorae, the genotypes 142 and 143-2 were selected as the most resistant to continue the breeding program.